Islamic Social Finance Optimalization For Economic Growth (Covid 19 In Indonesia) - Inggritia Safitri Masrul; Nurul Huda (Universitas Islam Negeri Alauddin Makassar, 2021)
Covid 19 has had a significant impact on financial institutions and the middle and lower classes in Indonesia. This study aims to optimize the ISF to increase economic growth amid the pandemic. This study uses a descriptive qualitative approach and library research techniques. Zakat can quickly raise funds for food aid programs, health, and other consumptive programs so that zakat can overcome the Covid 19 pandemic food crisis. Meanwhile, in the long term, zakat is optimized in education and economic programs. Infaq and alms can be obtained directly in cash from the zakat collection unit and the community. Waqf instruments are more intended for long-term periods, especially cash waqf in Cash Waqf Linked Sukuk to attract waqf for waqf and invest in developing infrastructure. The research concludes that ISF is a solution in increasing economic growth amid the Covid 19 pandemic by plotting these instruments in the short and long term. So that society can be resolved optimally, and the economy can survive and experience average growth again.